(untitled) (Western European Journal of Modern Experiments and Scientific Methods, 2024)
Determining the development of diseases in plants based on prognosis is widely used in modern agricultural technologies. This approach is based on a variety of data to predict the occurrence and spread of plant diseases. The article describes the types of forecasting and the stages of the forecasting scheme one by one